Shedding of proangiogenic microvesicles from hypertrophic scar myofibroblasts. Issue 1 (10th September 2020) - Laberge, Alexandra; Merjaneh, Mays; Arif, Syrine; Larochelle, Sébastien; Moulin, Véronique J.
Abstract: Hypertrophic scars are a common complication of burn injuries and represent a major challenge in terms of prevention and treatment. These scars are characterized by a supraphysiological vascular density and by the presence of pathological myofibroblasts (Hmyos) displaying a low apoptosis propensity. However, the nature of the association between these two hallmarks of hypertrophic scarring remains largely unexplored. Here, we show that Hmyos produce signalling entities known as microvesicles that significantly increase the three cellular processes underlying blood vessel formation: endothelial cell proliferation, migration and assembly into capillary‐like structures. The release of microvesicles from Hmyos was dose‐dependently induced by the serum protein α‐2‐macroglobulin. Using flow cytometry, we revealed the presence of the α‐2‐macroglobulin receptor—low‐density lipoprotein receptor‐related protein 1—on the surface of Hmyos. The inhibition of the binding of α‐2‐macroglobulin to its receptor abolished the shedding of proangiogenic microvesicles from Hmyos. These findings suggest that the production of microvesicles by Hmyos contributes to the excessive vascularization of hypertrophic scars. α‐2‐Macroglobulin modulates the release of these microvesicles through interaction with low‐density lipoprotein receptor‐related protein 1.